USING VIDEOS FOR VOCABULARY IMPROVEMENT IN ENGLISH CLASSES AS AN ADDITIONAL LANGUAGE - Grégis, Rosi Ana; Carvalho, Ana Paula (Revista Prâksis, 2019)
It is fact that technology has a great impact and effect on learning processes. This article aims at verifying if students are able to learn and retain vocabulary just by watching videos. Over and over, students suggest the use of videos in the classroom, but are they really effective or are they only used for students’ entertainment? Based on authors such as Muslem (2017), Mc Nulty (2012) and Wang (2015), we realize that videos increase fluency and stimulate the appropriate pronunciation of English language learners. In addition, videos combine visual and audio stimuli, are accessible to those who have not learned to read and write well, and provide context for learning (Fazey, 1999; Johnston, 1999; Burt, 1999). In the first moment of this research, students are exposed to a quiz in which they have to choose the correct meaning for a certain word or phrase. In the second phase, the same pupils watch 5 different videos, chosen by them before the first quiz from a YouTube channel. Last but not least, students answer a questionnaire again to check how much they have learned and retained new vocabulary. We notice that, possibly, students do not learn new vocabulary just by being exposed to videos, without meaningful pre, while and post activities. Keywords: Additional Language Teaching. English vocabulary acquisition. Videos in classroom. RESUMO É fato que a tecnologia tem grande impacto e efeito nos processos de aprendizagem. Este artigo visa verificar se os alunos são capazes de aprender e reter vocabulário somente assistindo vídeos. Cada vez mais os alunos sugerem o uso de vídeos em sala de aula. Contudo, vídeos são realmente eficazes ou são usados somente para o entretenimento dos alunos? Baseado em autores como Muslem (2017) e Mc Nulty (2012), percebemos que vídeos melhoram a fluência e estimulam a pronúncia adequada dos aprendizes da língua inglesa. Além disso, vídeos combinam estímulo visual e sonoro, são acessíveis àqueles que ainda não aprenderam a escrever e ler adequadamente, e proporcionam contexto para a aprendizagem (Fazey, 1999; Johnston, 1999). No primeiro momento desta pesquisa, os alunos são expostos a um questionário no qual eles têm que escolher o significado correto de determinada palavra ou expressão. Na segunda fase, os mesmos estudantes assistem a 5 vídeos diferentes, escolhidos por eles, antes do primeiro questionário, de um canal do YouTube. Por último, os alunos respondem novamente ao questionário a fim de verificar o quanto eles aprenderam e retiveram o novo vocabulário. Percebemos que, possivelmente, os alunos não aprendem novas palavras de vocabulário somente através de sua exposição a vídeos, sem que realizem atividades relacionadas a eles antes, durante e depois de assisti-los. Palavras-chave: Ensino de língua adicional. Aquisição de vocabulário em língua inglesa. Vídeos em sala de aula.